2022
DOI: 10.3390/molecules27227855
|View full text |Cite
|
Sign up to set email alerts
|

Novel Uracil-Based Inhibitors of Acetylcholinesterase with Potency for Treating Memory Impairment in an Animal Model of Alzheimer’s Disease

Abstract: Novel derivatives based on 6-methyluracil and condensed uracil, 2,4-quinazoline-2,4-dione, were synthesized with terminal meta- and para-benzoate moieties in polymethylene chains at the N atoms of the pyrimidine ring. In the synthesized compounds, the polymethylene chains were varied from having tris- to hexamethylene chains and quaternary ammonium groups; varying substituents (ester, salt, acid) at benzene ring were introduced into the chains and benzoate moieties. In vivo biological experiments demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Previously, we have studied the alkylation of trifluoromethylsubstituted 2-thiouracil 5c with 2-bromoacetophenone. [86] Based on the data of 2D NMR ( 1 H-1 H COSY, 1 H- 13 C HSQC, and HMBC), it was found that alkylation proceeds at the O and S atoms. In the 13 T A B L E 1 Substituents and yields for compounds 6, 7, 8a,b, 9, 10a,c, 11a-c, 12a-c, and 13a-c.…”
Section: Chemistrymentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we have studied the alkylation of trifluoromethylsubstituted 2-thiouracil 5c with 2-bromoacetophenone. [86] Based on the data of 2D NMR ( 1 H-1 H COSY, 1 H- 13 C HSQC, and HMBC), it was found that alkylation proceeds at the O and S atoms. In the 13 T A B L E 1 Substituents and yields for compounds 6, 7, 8a,b, 9, 10a,c, 11a-c, 12a-c, and 13a-c.…”
Section: Chemistrymentioning
confidence: 99%
“…[10] Initially, cholinergic therapy for AD was aimed at inhibiting acetylcholinesterase (AChE) as the main enzyme hydrolyzing the neurotransmitter acetylcholine. [11][12][13][14] The therapeutic effect of AChE inhibitors is due to an increase in the concentration and duration of action of acetylcholine in cholinergic synapses. [15] Butyrylcholinesterase (BChE) also takes part in the process of acetylcholine hydrolysis and is able to compensate for some of the functions of AChE, thereby improving cholinergic neurotransmission and, as a consequence, cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations